Developing Mathematics Instructional Materials (Research, Society and Development, 2019)
This study was aimed to develop mathematics instructional material in education science faculty of Batanghari University, Jambi. This research used Instructional Developmental Model. Then, several tests were also conducted such as one to one learner; small group and field trial. Afterwards, the research subjects are involving the 6th semester students along 2017/2018 period. The results then presented in validation percentage which were including design validation amounted 92,71%; media validation amounted 89,78% and material validation amounted 92,5%. Moreover, the result of one to one assessment was 97,2%, small group 93% and field trial 88,63%. Thus, from the validation and assessment conducted, then mathematics instructional material was worthy to be applied.